KARAKTERISTIK DAN MODEL PENGERINGAN LAPISAN TIPIS DAGING BUAH PALA (Myristica fragrans Houtt) MENGGUNAKAN EXPERIMENTAL DRYER - Frisela Groria Koloay; Lady Lengkey; Frans Wenur (COCOS, 2017)
ABSTRAC Drying the nutmeg flesh with a thin layer method is carried out by using an experimental dryer. The objectives of this study were to study of drying air temperature and humidity on the drying of nutmeg flesh and to develop a mathematical model to estimates the drying curves. The experimental dryer is modified at Workshop of Agricultural Engineering study program University of Sam Ratulangi. The drying temperature is arranged at 60˚C. Simple method using an excel software is used in the analysis of raw data obtained from the drying experiment. The results showed the dryer air temperature in the dryer distribution and fluctuate in 52.1-62. 5˚C, while relative humidity ranges from 42-47%. It takes 3 hours to dry the nutmeg flesh until 12 – 14% moisture content. Mathematical model of the relation of water content and time is y = 1001.4e-0.023 with coefficient of determination (R²) = 0.9919. The mathematical model of drying rate versus time is y = 5.006e-0.016 with R² = 0.9662. While the mathematical model of drying rate versus moisture content is y = 1.5115e0.0036x with R² = 0.799. The models showed have a good in quality of the fit.Keywords: dry nutmeg, characteristics, drying model and thin layer